Human subsistence strategy in the Ordos Plateau, Inner Mongolia, China, during the Qin and Han dynasties: Using stable isotope analysis. (14th May 2021) - Hou, Liangliang; Hu, Chunbai; Wu, Tianhui; Zhao, Yanni; Deng, Hui; Guo, Yi
Abstract: This article aims to reveal the subsistence economy of the Qin and Han empires and why they continued to advance northward to defeat the Huns (Xiongnu 匈奴) and other grassland peoples in the Ordos Plateau. We present the δ 13 C and δ 15 N results for the dietary reconstruction of animals and humans from the Fuluta cemetery in the Ordos Plateau, a nomadic farming junction area, from the late Qin dynasty (221–207 BCE) to the Western Han dynasty (202 BCE to 8 AD). Results show that the δ 13 C and δ 15 N values for humans (−8.5 ± 0.4‰, 9.2 ± 0.5‰, n  = 29), pigs (−8.6 ± 1.4‰, 7.7 ± 1.1‰, n  = 3) and dogs (−9.1 ± 0.3‰, 7.7 ± 0.4‰, n  = 3) were generally higher than those for cattle (−15.7 ± 1.4‰, 6.5 ± 1.0‰, n  = 8) and sheep (−17.8 ± 0.9‰, 6.2 ± 1.6‰, n  = 11), indicating humans, pigs and dogs may have relied primarily on C4 ‐based food (millet), whereas cattle and sheep mainly relied on C3 ‐based food (wild plants). Related research shows that the diet of the population of the Fuluta cemetery was relatively homogenous and mainly based on millet agriculture and domestic animals, such as pigs, indicating that millet‐based agriculture was narrowly focused on for subsistence in the frontier region of northern China. The results of stable isotope work of the past populations in the surrounding areas of the Ordos Plateau from the period of the late Western Zhou dynasty (1046–771 BCE) to the Han dynasties (202 BCE to 220 AD) show trends of northward advancement and stability of the agricultural economy were constantly strengthening. Therefore, agriculturalization in the Ordos Plateau may have been the motivating force for Qin and Han imperial expansion into the frontier region.